Effects of Inhaled Dexamethasone/Ciprofloxacin on Acute Subglottic Stenosis in a Rabbit Model - I‐Chun Kuo; Catherine K. Hart; Isabelle M. Gengler; Alessandro deAlarcón (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objectives Subglottic stenosis (SGS) is a challenging complication post‐airway interventions. Effective preventive strategies lack sufficient evidence. This study investigated the preventive effect of inhalation therapy with dexamethasone/ciprofloxacin on acute SGS in a rabbit model. Methods Twenty New Zealand White rabbits underwent subglottic injury via endoscopy and received inhalation therapy twice daily starting on the injury day. Group 1 (n = 4) received saline for 5 days and was sacrificed on day 5; Group 2 (n = 4) received dexamethasone/ciprofloxacin for 5 days and was sacrificed on day 5; Group 3 (n = 4) received the same therapy for 5 days and survived for one week, and was sacrificed on day 15; Group 4 (n = 4) received the therapy for 10 days and was sacrificed on day 15; Group 5 (n = 4) received the therapy for 10 days and survived for one week, and was sacrificed on day 22. Rabbits underwent repeat endoscopy and were euthanized at the designated time point. Histological measurements were analyzed statistically. Results Histological analysis revealed median cricoid lumen measurements of 20.01 ± 1.42 mm2 for group 1, 17.94 ± 3.05 mm2 for group 2, 14.84 ± 2.55 mm2 for group 3, 17.18 ± 5.31 mm2 for group 4, and 11.87 ± 5.68 mm2 for group 5. No significant differences were found between treatment and control groups (p = 0.486) or between 5‐day and 10‐day treatments (p = 0.686). Multivariate statistical analysis indicated that cessation of inhalation therapy (p < 0.05) and prolonged survival (p < 0.05) were associated with shorter cricoid lumen measurements. Conclusion Short‐term dexamethasone/ciprofloxacin inhalation does not prevent acute SGS. No improvements in cricoid lumen diameter were found. Extended survival correlated with shorter cricoid lumen, suggesting SGS progression is time dependent. Level of Evidence NA.